Icariin Activates Autophagy via Down-Regulation of the NF-κB Signaling-Mediated Apoptosis in Chondrocytes - Mi, Bobin; Wang, Junqing; Liu, Yi; Liu, Jing; Hu, Liangcong; Panayi, Adriana C.; Liu, Guohui; Zhou, Wu (Frontiers in Pharmacology, 2018)
Osteoarthritis (OA) is a common chronic and degenerative joint condition that is mainly characterized by cartilage degradation, osteophyte formation and joint stiffness. The NF-κB signaling pathways in inflammation, autophagy and apoptosis play a prominent role in the progression of OA. Icariin, a prenylated flavonol glycoside extracted from Epimedium, have been proven to exert anti-osteoporotic and anti-inflammatory effects in OA. However, the action mechanisms of its effect on chondrocytes has yet to be elucidated. In the present study, we demonstrated that the in vitro therapeutic effects of icariin on rat chondrocytes in a dose-dependent manner. We found that TNF-α induced the production of IL-1, IL-6, IL-12, reactive oxygen species (ROS), nitric oxide (NO), Caspase3 and Caspase 9 in chondrocytes. We also provided evidence that TNF-α inhibited autophagy markers (Atg 5, Atg 7) and prevented LC3 I translate to LC3 II. Furthermore, TNF-α induced matrix metalloproteinase (MMP)3 and MMP9 expression. The negative effects of TNF-α on chondrocytes can be partially blocked by treating with icariin or ammonium pyrrolidinedithiocarbamate (PDTC, an NF-κB inhibitor). The present study data also suggested that icariin suppressed both TNF-α-stimulated p65 nuclear translocation and IκBα protein degradation. These results indicated that icariin protected against OA by suppressing inflammatory cytokines and apoptosis, through activation of autophagy via NF-κB inhibition. In conclusion, icariin appears to favorably modulate autophagy and apoptosis in chondrocytes making it a promising compound for cartilage tissue engineering in the treatment of OA.